Sunitinib for adenocarcinoma of the rete testis: a case report - Li, Kezhen; Chen, Di; He, Mingdong; Yu, Jun; Mi, Hua (Frontiers in Oncology, 2024)
Background Adenocarcinoma of the rete testis (AORT) is an extremely rare and aggressive tumor with a poor prognosis. Its etiology and pathological characteristics have not been extensively studied, making accurate diagnosis and appropriate management challenging. AORT, an invasive testicular tumor with a mortality rate of 46%, treatment typically involves radical orchiectomy, retroperitoneal pelvic lymph node dissection (RPLND), adjuvant chemotherapy, and/or ongoing monitoring, but the response to conventional radiation and chemotherapy is limited. At present, no effective targeted therapy for AORT has been found. Case description In this case report, we present the clinical scenario of a 50-year-old male patient initially diagnosed with a right testicular hydrocele, who subsequently underwent eversion of the parietal tunica vaginalis. Postoperative pathological analysis revealed metastatic clear cell renal cell carcinoma (ccRCC). PET/CT demonstrated findings suggestive of left renal upper pole carcinoma with involvement of the right scrotum, para-aortic region, bilateral iliac vessels, bilateral inguinal region, and multiple metastases. Sunitinib, a tyrosine kinase inhibitor, is commonly employed in the treatment of ccRCC. The patient underwent treatment with sunitinib for a duration of 20 months, resulting in the inactivation of multiple metastases. Following this, a radical orchiectomy was performed, and the postoperative pathology confirmed the presence of AORT. This article provides a comprehensive account of the patient's medical history, diagnostic process, treatment modalities, and subsequent follow-up observations. Conclusions This case report highlights the successful use of targeted therapy with sunitinib in a patient with AORT. The patient showed a positive response to targeted therapy. This study not only provides a novel foundation for the treatment of AORT, but also offers valuable insights for future treatment strategies in managing this particular form of testicular cancer.